The effect of learning outcomes on subject of creative product and entrepreneurship, family support to entrepreneurial interest in students of fashion management SMKN 6 Padang - Oktaviani, Vina; Yulastri, Asmar (Universitas Negeri Padang, 2020)
This research aims to show the effect of learning outcomes on subject of creative product and entrepreneurship, family support to entrepreneurial interest in students of Fashion Management SMKN 6 Padang. This research used quantitative research method with a correlational approach. The population of this research was all students of class XII of the Fashion Management SMKN 6 Padang with total of 122 students with the sample was 92 students which was taken on proportional random sampling. Data collection technique used a research questionnaire. The questionnaire try out was tested on 30 students of the population who were not included in the sample, then conducted a validity and reliability test. Testing of the data analysis requirement and hypotheses with the normality test, linearity test, multicollinearity test and regression analysis. The result of the analysis obtained the learning outcomes of creative product and entrepreneurship (X1) had an effect on Entrepreneurial Interest (Y), with a significance value of 0.007<0.05, Fcalculate> Ftable (10.753>2.000) and an effect contribution of 53,1%. Family support (X2) had an effect on Entrepreneurial Interest (Y), with a significance value of 0,000<0.05, Fcalculate> Ftable (10.385> 2.000) and effect contribution of 64.5%. Learning Outcomes on Subject for Creative Product and Entrepreneurship (X1), Family Support (X2) had a positive and significant effect respectively on Entrepreneurial Interest (Y) students of the Fashion Management SMKN 6 Padang, with a significance value of 0.000 < 0.05 and Fcalculate> Ftable (42,662 > 4.04) with an effect contribution of 62.7%.